The Benefit and Importance of Mobile Satellite Signal in Northern Nigeria: GPS Approach - Abba, Ibrahim; Muhammad, Salisu; D. Bala, Lawan Bashir; Joseph, Emmanuel (Journal of Advanced Industrial Technology and Application, 2021)
A Handheld GPS receiver as tool for training college students on mobile satellite signal propagation was designed using Global Positioning System (GPS) approach. These refer to the experimental setup of the equipment that is the connection done between the GPS receiver with a computer. The satellite propagation data received from the GPS satellite can be recorded continuously with an updates rate of 2 seconds. The experiment was carried out in an open space environment at predetermine locations using simple setup, where a cheap, readily and available portable GPS receiver were connected to the computer to acquire propagation data. The computer was equipped with a self-developed package graphical user interface (GUI) monitoring the propagation information from the GPS satellites and saving the data. The developed system can be set up anywhere at any location. The sate-up will serve as a database for view and analysis of mobile satellite orbiting the sky of Northern part of Nigeria. Cost effective referring to a low-cost and readily available GPS receiver that can be easily set-up as compared to equipment designed specifically for an experimental purpose that is normally very expensive.